Features of Inner Position of Mother in IVF Women - Yakupova V.A.; Zakharova E.I. (Культурно-историческая психология, 2016)
This work aims to explore the features of inner position of mother in women who had underwent IVF (in vitro fertilisation) and how these features affect parenthood and child-adult relationships. The study involved 20 mother-baby dyads comprised of women who conceived naturally and 23 dyads comprised of women who had IVF (the infants were 6—12 months old). The mothers from the IVF group expressed more unconditional acceptance of their child and desire for body contact but were less likely to support the child’s initiative than the mothers from the first group. The features of parent-child relationships have a certain impact on the child’s development: the infants whose mothers are ready to support them are likely to be more active. The desire for close body contact is more expressed in those infants whose mothers touch, hug and carry them more frequently. The mothers from the IVF group perceive their parental duties in a positive way, but at the same time experience doubts in their parental competence and are likely to place excessive demands on themselves as mothers.